«La Celestina» 1499-1999: Selected papers from the International Congress in Commemoration of the Quincentennial Anniversary of «La Celestina». Ed de Ottavio Di Camillo y John O’Neill. New York, Hispanic Seminary of Medieval Studies, 2005 - Paolini, Devid (Celestinesca, 2021)
N/A